The Effect Of Work Stress, Work Load And Work Motivation On Job Satisfaction And Employee Performance Of The Department Of Culture, Youth And Sports Of Kapuas Regency - Roya Mersina; Lanny Purnama Kosasi (Sean Institute, 2022)
Roya Mersina (2022). The Influence of Work Stress, Workload and Work Motivation on Job Satisfaction and Employee Performance at the Department of Youth Culture and Sports, Kapuas Regency. Master of Management Masters Program STIE Pancasetia Banjarmasin, under the guidance of H. Nurus Sjamsi and HM Zaid Abdurrahman. The purpose of the study was to determine and analyze the effect of: (1) work stress on job satisfaction (2) workload on job satisfaction (3) work motivation on job satisfaction (4) work stress on performance (5) workload on performance (6) work motivation on performance (7) satisfaction with employee performance (8) work stress on performance through job satisfaction (9) workload on performance through job satisfaction, and (10) work motivation on performance through job satisfaction. Explanatory research method. The research population of all employees is 36 people with total sampling. Data collection through questionnaires and documentation were analyzed quantitatively through path analysis (path analysis). The results showed (1) work stress had a significant effect on job satisfaction (2) workload had a significant effect on job satisfaction (3) work motivation had a significant effect on job satisfaction (4) work stress had a significant effect on employee performance (5) workload has a significant effect on employee performance (6) work motivation has no significant effect on employee performance ((7) job satisfaction has a significant effect on employee performance (8) job satisfaction mediates the effect of work stress on employee performance (9) job satisfaction mediates the effect of workload on employee performance ( 10) job satisfaction mediates the effect of work motivation on employee performance at the Department of Culture, Youth and Sports, Kapuas Regency.